AN ANALYSIS OF PERFORMANCE MANAGEMENT SYSTEM FOR IMPROVING LOCAL GOVERNMENT - Sulistiani, Lilis Sri; Kismartini, Kismartini; Suwitri, Sri; Putranti, Ika Riswanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This paper will look at the success of a local government organization with the determination of organizational resources and the right performance management system in order to improve public services in the local government. This article aimed at finding out whether the performance management system is appropriate if it is implemented in the local government work environment. The research method used a literature study by analyzing previous research and other various reference sources, both from textbooks, national journals, and reputable international journals. As an analytical material, we provided an example of an analysis of the performance management system in Banyumas Regency Government. Based on this, it can be concluded that Banyumas Regency always strives to improve organizational performance and existing resources through the implementation of performance management practices although formally the Head of the Region has not yet established a performance management system that applies in Banyumas Regency